EFFECT OF âKOMBA-KOMBAâ PRUNING COMPOST AND PLANTING TIME OF MUNGBEAN IN INTERCROPPING WITH MAIZE ON YIELD AND SOIL FAUNA - Sabaruddin, Laode; Kilowasid, Laode Muhammad Harjoni; Syaf, Hasbullah (Faculty of Agriculture University of Brawijaya and Indonesian Agronomic Assossiation, 2013)
Soil fauna plays an important role in decomposition and nutrient mineralization. The objective of this research was to study the effect of